2014
DOI: 10.1007/s11195-014-9373-5
|View full text |Cite
|
Sign up to set email alerts
|

Experiences Shared Through the Interviews from Fifteen Mothers of Children with Cerebral Palsy

Abstract: The study utilized an interview format to examine the difficulties experienced by mothers of children with cerebral palsy. Interviews were conducted in the province of Zonguldak between December 2013 and February 2014, Turkey, at a special rehabilitation center with 15 children with cerebral palsy and their mothers registered at the center. A voice recorder was used during the interviews, but since the mothers expressed their unwillingness to have their voices recorded during the interviews when they talked ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 20 publications
1
4
1
1
Order By: Relevance
“…Our study found that the participant mothers spent most of their time on their children with CP and less on their husbands and their other children, which created problems within the family. Similar findings have also been noted by other studies (5,11,(22)(23)(24). Although the mothers are the most affected, having a child with CP hurts all family members and intra-family relationships.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our study found that the participant mothers spent most of their time on their children with CP and less on their husbands and their other children, which created problems within the family. Similar findings have also been noted by other studies (5,11,(22)(23)(24). Although the mothers are the most affected, having a child with CP hurts all family members and intra-family relationships.…”
Section: Discussionsupporting
confidence: 89%
“…This situation enhances the dependency of the children on their mothers. Increased dependence on mothers creates new problems for these mothers and harms their expectations, emotions, and feelings (5,23,27). In our study, participants expressed their concerns about the future.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Os trabalhos direcionados às dificuldades das mães ressaltaram a cultura e as condições sociais precárias que estariam permeando de maneira negativa os cuidados às crianças com PC (KURTUNCU et al, 2013;ST JOHN, 2012; KELLETT; ST JOHN, 2010). Kurtuncu et al (2014) deram voz às mães mulçumanas de 15 crianças com PC moradoras da Turquia e detectou sérias dificuldades que incluíam problemas nas relações pessoais, assim como nas relações conjugais, dificuldades no processo de inclusão social e dificuldades econômicas associadas aos cuidados e educação da criança com PC. Em consonância com estes achados, os trabalhos de Huang, Kellett e St John (2012) e Huang, Kellett e St John (2010) com 15 mães chinesas apontaram que mães de crianças com PC além de permanecerem solitárias no papel de cuidadoras principais, eram hostilizadas pelas famílias de seus maridos, tendo, portanto, pouco ou nenhum apoio nos cuidados aos seus filhos.…”
Section: Agrupamento: Experiências No Cuidado Diário (Sete Estudos)unclassified